Bereavement after the suicide of a significant other - Pompili, Maurizio (Medknow Publications & Media Pvt Ltd, 2013)
CONTEXT: It is estimated that approximately one in four people know someone who has taken their own life and that one suicide death leaves six or more suicide survivors. AIMS: The aim of this paper was to review the literature regarding the association between suicide and bereavement, focusing also on the supportive and therapeutic resources available for survivors. MATERIALS AND METHODS: Careful MedLine and PsycINFO searches for the period 1980-2013. RESULTS: The review of the literature indicates that emotional turmoil in suicide survivors may last a long time and, in some cases, may end with their own suicide. CONCLUSION: Future research should evaluate the efficacy of professional treatments and of support groups targeting suicide survivors. PRACTICE IMPLICATIONS: It is crucial to understand the bereavement process after the suicide of a significant other in order to provide proper care, reduce stigma, and improve the outcomes of related psychiatric conditions.